Living in the crosshairs: the untold stories of anti-abortion terrorism - Cohen, David S. (Oxford University Press, 2015)
"A chilling exposé of the threats, harassment, and worse that American abortion providers face on a daily basis-and groundbreaking remedies to stop it"--